2023
DOI: 10.1186/s13578-023-01040-4
|View full text |Cite
|
Sign up to set email alerts
|

Overview of multifunctional cysteinyl cathepsins in atherosclerosis-based cardiovascular disease: from insights into molecular functions to clinical implications

Abstract: Cysteinyl cathepsins (CTSs) are widely known to have a proteolysis function that mediates recycling of unwanted proteins in endosomes and lysosomes, and investigation of CTSs has greatly improved with advances in live-imaging techniques both in vivo and in vitro, leading to three key findings. (1) CTSs are relocated from the lysosomes to other cellular spaces (i.e., cytosol, nucleus, nuclear membrane, plasma membrane, and extracellular milieu). (2) In addition to acidic cellular compartments, CTSs also exert b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…The broader group of genes discussed, including CTSW and STAB1, have been linked to lipid processing and cardiovascular health. For example, CTSW has been studied for its role in HDL cholesterol metabolism and its potential impact on atherosclerosis ( Cheng et al, 2023 ), while STAB1 has been implicated in the clearance of atherogenic lipoproteins ( Verwilligen et al, 2022 ). These associations reinforce the systemic nature of blood as a reflection of lipid metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…The broader group of genes discussed, including CTSW and STAB1, have been linked to lipid processing and cardiovascular health. For example, CTSW has been studied for its role in HDL cholesterol metabolism and its potential impact on atherosclerosis ( Cheng et al, 2023 ), while STAB1 has been implicated in the clearance of atherogenic lipoproteins ( Verwilligen et al, 2022 ). These associations reinforce the systemic nature of blood as a reflection of lipid metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of chronic stress to enhance CTSK expression and activity probably contributed to adipose dysfunction mice under our condi-A recent comprehensive review documented the role cysteinyl cathepsins in metabolic cardiovascular disease. 22 Cathepsins function as modulators of cellular events (e.g., migration, proliferation, apoptosis) in various cell lines, and this modulation is dependent on the proteolytic and nonproteolytic functions of the respective cells. 43 It was reported that CTSL activity leads to an enhancement of human and murine pre-adipocyte lipid accumulation and adipogenesis by modulating fibronectin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine protease cathepsins were originally found to be localized to lysosomes and endosomes in humans and animals. 22 The main physiological function of cathepsins is to break down unwanted intracellular or endocytic proteins, but cathepsins also play an important role in pathological processes by regulating inflammation and immune responses through extracellular matrix remodeling, leukocyte recruitment, and cell adhesion. 23,24 Cathepsin K and DPP4 +/+ mice underwent stress exposure plus GLP-1 receptor agonist exenatide loading for 2 weeks and then were analyzed for stress-related biological and/ or morphological alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to CPS is also a comparatively intractable risk factor for thrombotic cardiocerebrovascular diseases (TCVDs) [ 5 9 ]. A 2023 review highlighted the close relationship between chronic stress and the prothrombotic state and thrombus formation in animal models and humans with TCVDs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%